The Effect of Closed Suction System Use on the Incidence of Ventilator-Associated Pneumonia (VAP) in Patients Receiving Mechanical Ventilation: A Systematic Literature Review - Eppy Setiyowati; Widayati Widayati; Samsudi Samsudi; Eka Sulistiyowati (Indonesian Journal of Global Health Research, 2026)
Ventilator-associated pneumonia (VAP) is one of the most common and serious infections in patients who use mechanical ventilation. It has an incidence of 5–50% and contributes to increased morbidity and mortality. One of the efforts to prevent Ventilator-associated pneumonia (VAP) is the endotracheal suctioning procedure. Currently, there are closed suction systems and open suction systems. However, scientific evidence regarding the effectiveness of closed suction systems in reducing the incidence of ventilator-associated pneumonia (VAP) remains variable. This study aimed to evaluate the effectiveness of closed versus open suction systems in preventing ventilator-associated pneumonia (VAP) in mechanically ventilated adult patients, This study is a systematic review of 13 articles published between 2020 until 2025, which were selected through the PRISMA-2020 process using databases such as Google Scholar, ScienceDirect, and Semantic Scholar. The inclusion studies involved adult patients who were mechanically ventilated for more than 48 hours and reported the incidence of ventilator–associated pneumonia (VAP) as the primary outcome. The review showed that most studies reported no significant difference between closed and open suction systems in reducing ventilator-associated pneumonia (VAP) (p < 0.05). However, several studies have shown additional clinical benefits of closed suction systems, including improved oxygenation, reduced hypoxia, delayed onset of VAP, and reduced end expiratory pressure (PEEP). One study reported a significant reduction in VAP when closed suction was combined with chlorhexidine flushing. The close suction system has not been conclusively proven to reduce the incidence of ventilator-associated pneumonia (VAP), however, it provides valuable clinical and safety benefits.